NF‐Y plays essential roles in flavonoid biosynthesis by modulating histone modifications in tomato. Issue 6 (21st December 2020) - Wang, Jiafa; Li, Guobin; Li, Changxing; Zhang, Chunli; Cui, Long; Ai, Guo; Wang, Xin; Zheng, Fangyan; Zhang, Dedi; Larkin, Robert M.; Ye, Zhibiao; Zhang, Junhong
Summary: NF‐Y transcription factors are reported to play diverse roles in a wide range of biological processes in plants. However, only a few active NF‐Y complexes are known in plants and the precise functions of NF‐Y complexes in flavonoid biosynthesis have not been determined. Using various molecular, genetic and biochemical approaches, we found that NF‐YB8a, NF‐YB8b and NF‐YB8c – a NF‐YB subgroup – can interact with a specific subgroup of NF‐YC and then recruit either of two distinct NF‐YAs to form NF‐Y complexes that bind the CCAAT element in the CHS1 promoter. Furthermore, suppressing the expression of particular NF‐YB genes increased the levels of H3K27me3 at the CHS1 locus and significantly suppressed the expression of CHS1 during tomato fruit ripening, which led to the development of pink‐coloured fruit with colourless peels. Altogether, by demonstrating that NF‐Y transcription factors play essential roles in flavonoid biosynthesis and by providing significant molecular insight into the regulatory mechanisms that drive the development of pink‐coloured tomato fruit, we provide a major advance to our fundamental knowledge and information that has considerable practical value for horticulture.